The principle of Restorative Justice in sentencingIn the 2023 Criminal Code - Ningtias, Ayu Dian; Nahdliyah, Hadziqotun; Nugroho, Fajar Seto; Akbari, Damai Al (Jurnal Independent, 2023)
Abstract the concept and analysis of the regulation of the principles of restorative justice in the 2023 Criminal Code is a solution for imposing sentences on minor criminal cases and avoiding short-term imprisonment, as well as preventing this. Application of the principle that the aim is to prevent people from being punished. This is for protection and is seen in society as an effort to rehabilitate the perpetrator. By upholding a sense of justice and the benefits of the law, as well as Pancasila values in law enforcement and criminal objectives, implementing the principle of judge's forgiveness in the 2023 Criminal Code means that there are defendants who have not been found guilty or served a sentence, even though their charges have been legally and convincingly proven.